Financial Policy Workshops : The Case of Kenya. (International Monetary Fund, 1985)
This book, written by the staff of the IMF Institute, offers a series of workshops on Kenya that are used as a case study in the Institute's course on Financial Analysis and Policy for officials of IMF member countries. The workshops combine theory and practice for a better understanding of the use of major financial policy instruments in the management of national economies.